Investigation of electric fields inside and outside a magnetised cold plasma sphere - 李应乐 王明军 董群峰 (Chinese physics B, 2010)
Based on the scales transformation of electromagnetic theory, the analytical expressions of electric fields inside and outside a magnetised cold plasma sphere are presented by reforming the spherical electromagnetic parameter. The obtained results are in good agreement with that in the literature. The angle between the direction of inside field and that of outside field is derived. In S wave band, calculations for the effects induced by parameters of the inner field are established. Simulations show that the angle between incident field and the outside magnetic field influences the inner field remarkably. The inner field will increase as the electron density increases. The inner field varies with frequency nonlinearly. There is an angle between the inner field and the incident field, it changes nonlinearly with the frequency.